Instigating prevalent abiotic stress resilience in crop by exogenous application of phytohormones and nutrient - Swain, Rinny; Sahoo, Smrutishree; Behera, Mamata; Rout, Gyana Ranjan (Frontiers in Plant Science, 2023)
In recent times, the demand for food and feed for the ever-increasing population has achieved unparalleled importance, which cannot afford crop yield loss. Now-a-days, the unpleasant situation of abiotic stress triggers crop improvement by affecting the different metabolic pathways of yield and quality advances worldwide. Abiotic stress like drought, salinity, cold, heat, flood, etc. in plants diverts the energy required for growth to prevent the plant from shock and maintain regular homeostasis. Hence, the plant yield is drastically reduced as the energy is utilized for overcoming the stress in plants. The application of phytohormones like the classical auxins, cytokinins, ethylene, and gibberellins, as well as more recent members including brassinosteroids, jasmonic acids, etc., along with both macro and micronutrients, have enhanced significant attention in creating key benefits such as reduction of ionic toxicity, improving oxidative stress, maintaining water-related balance, and gaseous exchange modification during abiotic stress conditions. Majority of phytohormones maintain homeostasis inside the cell by detoxifying the ROS and enhancing the antioxidant enzyme activities which can enhance tolerance in plants. At the molecular level, phytohormones activate stress signaling pathways or genes regulated by abscisic acid (ABA), salicylic acid (SA), Jasmonic acid (JA), and ethylene. The various stresses primarily cause nutrient deficiency and reduce the nutrient uptake of plants. The application of plant nutrients like N, K, Ca, and Mg are also involved in ROS scavenging activities through elevating antioxidants properties and finally decreasing cell membrane leakage and increasing the photosynthetic ability by resynthesizing the chlorophyll pigment. This present review highlighted the alteration of metabolic activities caused by abiotic stress in various crops, the changes of vital functions through the application of exogenous phytohormones and nutrition, as well as their interaction.